PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 016 SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Kurniaman, Otang; ', Jusmaniar; ', munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study in background backs by low learning outcomes IPS Grade IV SDN 016 Sekeladi ie with an average of 56.0. Of the 15 students, only 6 students achieve the learning outcomes and 9 students who do not achieve the learning outcomes of a predefined KKM is 65. This research aims to improve learning outcomes through the application of learning models IPS quantum teaching in grade IV SDN 016 Sekeladi Tanah Putih Rokan Hilir district. This research is a classroom action research. Cycle stages in the repair of this study megalami twice the cycle in which the data were collected through observation of teacher activity and student activity observation during the learning process and the results of daily tests. The results showed that the application of quantum model of teaching can improve learning outcomes IPS. This proved the average value obtained by students each cycle has increased. The average yield obtained preliminary data 56.0. After improvement of learning through quantum model of teaching in the first cycle 64.0. Dilanjutakan to the second cycle on average earn 73.3. Mean that teachers in the application of quantum learning model of teaching in social studies in accordance with the abilities of students so that the resulting self-confidence in students to absorb the lessons and can improve learning outcomes IPS. The activities of teachers in the application of Quantum models of teaching have increased in the first cycle the first meeting increased 58.33% 68.75% Second meeting, the second cycle of the first meeting to meeting increased 70.83% to 81.25% II. Student activity in the application of Quantum Teaching models to improve learning outcomes IPS has increased from cycle to cycle. Student activity first cycle of meetings I got a score of 33 with a percentage of 68.75%, while the second meeting got a score of 34 percentage 70.83%. Cycle II perteman I got a total score of 35 with a percentage of 72.91% and the second cycle of the second meeting got a total score of 38 with the percentage becomes 79.16%.Â Keywords: Model Quantum Teaching, Learning Outcomes IPS